I. 2y² - 3y – 14 = 0

II. 3x² - 7x + 4 = 0

I. 2y² - 3y – 14 = 0 2y² - 7y + 4 y – 14 = 0 y (2 y – 7) + 2( 2 y – 7) = 0 (y + 2) (2 y – 7) = 0 ∴ y = -2, 7/2 II. 3x² - 7x + 4 = 0 3x² - 4x - 3 x + 4 = 0 x (3 x – 4) – 1 (3 x – 4) = 0 ∴ x = 1, 4/3 Hence, relationship cannot be established between x and y Alternate Method: if signs of quadratic equation is - ve and -ve respectively then the roots of equation will be -ve and +ve. (note: -ve sign will come in smaller root) So, roots of first equation = y = -2, 7/2 if signs of quadratic equation is - ve and +ve respectively then the roots of equation will be +ve and +ve. So, roots of second equation = x = 1, 4/3 After comparing we can conclude that relationship cannot be established.

- I. 6p² + 17p + 12 = 0 II. 12q² - 25q + 7 = 0
- Quantity I: The price of rice is decreased by 30%, by how much % the consumption is increase so that the expenditure will decreased by 10%? Quantity II: A man spends Rs. 45,600 out of his income 68,400. If his income and expenditure are increased by 19% and 13%. Find the percentage change in his savings.
- I. 2b
^{2}- 37b + 143 = 0 II. 2a^{2}+ 15a - 143 = 0 - I. x
^{2}– 9x + 18 = 0 II. y^{2}– 5y + 6 = 0 - I. 10x² - 11x + 3 = 0 II. 42y² - 23y – 10 = 0
- I. 8x – 3y = 85 II. 4x – 5y = 67
- I. x² + 11x + 24 = 0 II. y² + 17y + 72 = 0
- I. 2x
^{2 }+ 5x + 2 = 0 II. 4y^{2 }= 1 - I. 6x² - 49x + 99 = 0 II. 5y² + 17y + 14 = 0
- I. 2x² - 9x + 10 = 0 II. 3y² + 11y + 6 = 0

More Quadratic equation Questions

×

×